Comparative Assessment of Coarse Aggregate Collected from Tinau River and Banganga River - Lacoul, N.; Pandey, Y. L. (Journal of Lumbini Engineering College, 2024)
This study focuses on the physical and mechanical parameters among various properties of coarse aggregates from Tinau River and Banganga River, studies the variation in compressive strength of concrete cubes made of coarse aggregates from respective sources and their economic assessment for use in various construction projects. The result show that in terms of physical and mechanical properties, aggregates of Tinau River were found slightly better than those of Banganga River. The variation in compressive strength of concrete mix due to change in source is significant for rich mix concrete (1:1.5:3) while there is less significant variation in case of lean mix concrete (1:3:6) and (1:2:4) which shows that the variation increases with the rise in grade of concrete. The economic analysis conducted on the basis of mix design concluded that the difference in cost for producing 1m3 of concrete using coarse aggregate from Tinau River and Banganga River is Rs. 20.40 and the percentage of saving in cost of concrete is only 0.22%. Overall, this research can be valuable to engineers and researchers working in the field of infrastructure development projects.